Stem cell dynamics in the hair follicle niche - Rompolas, Panteleimon (2013)
Hair follicles are skin appendages of the mammalian skin that have the ability to periodically and stereotypically regenerate in order to continuously produce new hair over our lifetime. The ability of the hair follicle to regenerate is due to the presence of stem cells that along with other cell populations and non-cellular components, including molecular signals and extracellular material, make up a niche microenvironment. Mounting evidence suggests that the niche is critical for regulating stem cell behavior and thus the process of regeneration. Here we review the literature concerning past and current studies that have utilized mouse genetic models, combined with other approaches to dissect the molecular and cellular composition of the hair follicle niche. We also discuss our current understanding of how stem cells operate within the niche during the process of tissue regeneration and the factors that regulate their behavior.